Serializing Racial Subjects: The Stagnation and Suspense of the O.J. Simpson Saga - Foley, Megan (The Quarterly journal of speech, 2010)
While critiques of racial essentialism have demonstrated decisively that race is rhetorically contingent, institutions of white privilege nevertheless remain distressingly durable. The continuing media coverage of Orenthal James "O.J." Simpson since his 1995 acquittal exemplifies this chronic temporality of whiteness discourse. Over time, the Simpson case has become a series that gradually coordinated "black" and "white" collective subjects by stagnating and suspending the popular attachment to Simpson. The serial form eventually unmarked these racialized subject-positions, while retaining the white subject-position as a seemingly race-neutral norm. Serial temporality normalizes whiteness through a circular rhythm that vacillates between the disavowal of and possessive investment in white privilege.